BUREAUCRATIC REFORM IN ACHIEVING INTEGRITY ZONE: CASE STUDY AT THE TRANSPORTATION AGENCY OF BOJONEGORO REGENCY - Risma Yuliyanti; Ana Kumalasari; Rupiarsieh Rupiarsieh (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
This study aims to explore how bureaucratic reform has achieved integrity zones in the Bojonegoro Regency Transportation Agency. This study highlights the achievements and titles earned by the Bojonegoro District Transportation Agency as a Corruption-Free Zone. The research approach used is a descriptive qualitative case study. This study employs data collection methods that include interviews, documentation, and observation. Data analysis techniques use NVivo 12 Pro software. The primary concept employed in this study is the concept of bureaucratic reform in the development of integrity zones, as outlined in PERMENPAN-RB No. 90 of 2021 and Kolthoff's Public Integrity theory. The findings show that bureaucratic reform at the Bojonegoro district transportation agency has been progressing well, with the commitment of leaders and employees, as evidenced by employees' performance in maintaining the title of a corruption-free region. Challenges arise from service users' resistance, low understanding of service users regarding the complaint mechanism, and a failure to uphold the value of honesty among technical staff in the vehicle inspection service unit. This study recommends strengthening integrity values for all employees, optimizing the dissemination of service applications and complaint systems to the public, and increasing supervision to ensure the sustainability of the Integrity Zone.